Mathematical modelling of military operations - Misevičius, G.; Pakalnytė, V.; Pincevičius, A.; Eidukevičius, R.; Rakauskas, R. - J. (Nonlinear Analysis: Modelling and Control, 1998)
The aim of this paper is to show how the theory of systems of differential equations may be applied both to describe the battle actions and to control the trajectory of projectiles. We will restrict our attention to deterministic cases. Those cases are not well adapted to the real situation and must be treated as the first approach.
Keywords: none